Task-based language teaching to improve EFL tenth graders’ speaking skills at a public school in Cali (2023)
Previous investigations have reported the effectiveness of Task-Based Language Teaching (TBLT) in enhancing EFL (English as a Foreign Language) students’ speaking performance. Although TBLT is a current and relevant communicative language teaching methodology, English language teaching in public schools still focuses on linguistic aspects and traditional teaching practices. As a result, EFL learners’ speaking skills are low. Most studies in our national and local contexts have predominantly used qualitative research to explore the TBLT impact on EFL learners’ performance. In contrast, very few have implemented both qualitative and quantitative approaches to report its effectiveness. To contribute pedagogically and methodologically to this area, this mixed-method study investigated the effectiveness of TBLT in improving tenth graders’ English oral skills in a public school in Cali. To this end, we implemented mixed-methods research with 23 students from an intact class. Qualitative data were collected through class observations, an initial student’s questionnaire, a teacher’s interview to identify the students’ needs and perceptions of oral performance, a journal, a final students’ questionnaire, and a final teacher’s interview to evidence TBLT usefulness. Content analysis was used to analyze qualitative data. Quantitative data were collected through a placement test, a pre-test, and a post-test to identify the students’ initial and final language levels and the impact of TBLT on their oral performance across several facets. Quantitative data were analyzed using a scoring rubric and paired-samples t-tests. We implemented one task cycle for over eight weeks (twenty-one hours of intervention), integrating all language skills with a focus on oral skills. The results revealed that TBLT helped the students improve vocabulary, grammar, and task fulfillment and to a lesser extent pronunciation, fluency and interaction and communication, which was expected because of the shortness of the intervention. As well, this methodology was also effective in improving EFL learners' motivation, participation, and engagement in the activities throughout the TBLT implementation. The students’ perceptions of oral proficiency also improved. Although TBLT can be implemented in a public-school context with teenagers, it requires adequate conditions for better results. These conditions include more hours assigned to the English class, continuity, and teachers’ training and enactment of TBLT. The results have implications for EFL teachers, particularly in public schools.